2021
DOI: 10.1080/0020739x.2021.1961171
|View full text |Cite
|
Sign up to set email alerts
|

How an inquiry-oriented textbook shaped a calculus instructor’s planning

Abstract: We investigate how an inquiry-oriented, dynamic, open-source calculus textbook shaped one college instructor's planning. We rely on Dietiker et al. 's [(2018). Research commentary: Curricular noticing: A framework to describe teachers' interactions with curriculum materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to Ball and Cohen (1996), there is a close relationship between mathematics textbooks and teachers' practice. While teachers rely on their professional experiences and beliefs to interpret the content within a textbook (Liakos et al, 2021), they still look to textbooks as a "dialogic partner" (Dietiker et al, 2018, p. 522) that contains vital material to be used in the classroom. Liakos et al (2021) conducted a qualitative study of the curriculum planning activities of a seasoned teacher who switched from teaching calculus with a traditional approach to teaching reform-based calculus.…”
Section: Relationships Between Mathematics Textbooks and Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ball and Cohen (1996), there is a close relationship between mathematics textbooks and teachers' practice. While teachers rely on their professional experiences and beliefs to interpret the content within a textbook (Liakos et al, 2021), they still look to textbooks as a "dialogic partner" (Dietiker et al, 2018, p. 522) that contains vital material to be used in the classroom. Liakos et al (2021) conducted a qualitative study of the curriculum planning activities of a seasoned teacher who switched from teaching calculus with a traditional approach to teaching reform-based calculus.…”
Section: Relationships Between Mathematics Textbooks and Teachersmentioning
confidence: 99%
“…While teachers rely on their professional experiences and beliefs to interpret the content within a textbook (Liakos et al, 2021), they still look to textbooks as a "dialogic partner" (Dietiker et al, 2018, p. 522) that contains vital material to be used in the classroom. Liakos et al (2021) conducted a qualitative study of the curriculum planning activities of a seasoned teacher who switched from teaching calculus with a traditional approach to teaching reform-based calculus. Observing the teacher using the textbook extensively in his planning and adding his own related materials, they concluded that the textbook significantly influenced his teaching.…”
Section: Relationships Between Mathematics Textbooks and Teachersmentioning
confidence: 99%